2013
DOI: 10.2106/jbjs.l.01497
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Platelet-Rich Plasma on Autologous Osteochondral Transplantation

Abstract: The use of PRP as a biological adjunct to autologous osteochondral transplantation has the clinical potential to enhance graft integration, decrease cartilage degeneration, and improve clinical outcomes of autologous osteochondral transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 46 publications
0
42
1
Order By: Relevance
“…Therefore it is important of the interface integration for the cartilage repair. PRP may enhance cartilage repair at the graft interface through recruitment of mesenchymal stem cells49. The introduction of rBMSC in PRP scaffolds may thus facilitate the recruitment efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is important of the interface integration for the cartilage repair. PRP may enhance cartilage repair at the graft interface through recruitment of mesenchymal stem cells49. The introduction of rBMSC in PRP scaffolds may thus facilitate the recruitment efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Smyth et al[56] showed in a systematic review that 18 of 21 (85.7%) basic science papers reported positive effects of PRP on cartilage repair. Additionally, Smyth et al[57] found in a rabbit model, that application of PRP at time of AOT improved the integration of the osteochondral graft at the cartilage interface and decreased graft degeneration. In clinical studies, Guney et al[58] performed a randomized control trial in 19 OLT patients and reported that BMS with PRP had better functional outcomes when compared with BMS alone.…”
Section: Biologic Augumentation For Cartilage Repairmentioning
confidence: 99%
“…However, the lack of proper controls necessitates further investigations regarding the clinical use of PRP for OA. In an acute femoral defect model, the treatment of osteochondral grafts with PRP prior to implantation actually led to the improvement of graft-host integration when compared to grafts treated with saline solution [162], further indicating that PRP can decrease cartilage degeneration via the inhibition of inflammatory signals and the induction of neo-cartilage integration. Given the multifarious properties of PRP, future combinatory strategies can aim to leverage specific PRP effects through the co-delivery of synergistic or inhibitory factors.…”
Section: Strategies For Controlling Delivery Of Biologicsmentioning
confidence: 99%